Seabird Trophic Position Across Three Ocean Regions Tracks Ecosystem Differences - Gagné, Tyler O.; Hyrenbach, K. David; Hagemann, Molly E.; Bass, Oron L.; Pimm, Stuart L.; MacDonald, Mark; Peck, Brian; Houtan, Kyle S. Van (Frontiers in Marine Science, 2018)
We analyze recently-collected feather tissues from two species of seabirds, the sooty tern (Onychoprion fuscatus) and brown noddy (Anous stolidus), in three ocean regions (North Atlantic, North Pacific, South Pacific) with different human impacts. The species are similar morphologically and are similar in the trophic levels from which they feed within each location. In contrast, we detect reliable differences in trophic position amongst the regions. Trophic position appears to decline as the intensity of commercial fishing increases, and is at its lowest in the Caribbean. The spatial gradient in trophic position we document in these regions exceeds those detected over specimens from the last 130 years in the Hawaiian Islands. Modeling suggests that climate velocity and human impacts on fish populations strongly align with these differences.